2022
DOI: 10.1371/journal.pone.0275829
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in biomass and related traits among four generations advanced lines of Cleome (Gynandropsis gynandra L. (Briq.))

Abstract: Gynandropsis gynandra (spider plant) is an African traditional leafy vegetable rich in minerals, vitamins and health-promoting compounds with potential for health promotion, micronutrients supplementation and income generation for stakeholders, including pharmaceutical companies. However, information on biomass productivity is limited and consequently constrains breeders’ ability to select high-yielding genotypes and end-users to make decisions on suitable cultivation and production systems. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Previous research has found a positive and strong correlation between Ly and Ph, Sd, Ll and Lw ( Zakaria et al., 2017 ). Similarly, Kangai Munene et al., 2018 ; Houdegbe et al., 2022 discovered a positive and strong relationship between Ph and Nl.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous research has found a positive and strong correlation between Ly and Ph, Sd, Ll and Lw ( Zakaria et al., 2017 ). Similarly, Kangai Munene et al., 2018 ; Houdegbe et al., 2022 discovered a positive and strong relationship between Ph and Nl.…”
Section: Discussionmentioning
confidence: 83%
“…Vitamins C, A, E, B1, B2, and B9 as well as minerals including iron, zinc, calcium, copper, potassium, magnesium, manganese, phosphorus, and sodium are abundant in the species’ leaves and surpass those in most exotic vegetables ( Abukutsa-Onyango, 2005 ; Odhav et al., 2007 ; Uusiku et al., 2010 ; Singh et al., 2013 ; Houdegbe et al., 2022 ). The leaves of G. gynandra are also high in proteins and fatty acids ( Mnzava, 1990 ; Van Der Walt et al, 2009 ), as well as essential amino acids (histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, valine).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation